Common barriers, but temporal dissonance: Genomic tests suggest ecological and paleo‐landscape sieves structure a coastal riverine fish community - Thomaz, Andréa T.; Knowles, L. Lacey (Molecular ecology, 2020)
Assessments of spatial and temporal congruency across taxa from genetic data provide insights into the extent to which similar processes structure communities. However, for coastal regions that are affected continuously by cyclical sea‐level changes over the Pleistocene, congruent interspecific response will not only depend upon codistributions, but also on similar dispersal histories among taxa. Here, we use SNPs to test for concordant genetic structure among four codistributed taxa of freshwater fishes (Teleostei: Characidae) along the Brazilian Atlantic coastal drainages. Based on population relationships and hierarchical genetic structure analyses, we identify all taxa share the same geographic structure suggesting the fish utilized common passages in the past to move between river basins. In contrast to this strong spatial concordance, model‐based estimates of divergence times indicate that despite common routes for dispersal, these passages were traversed by each of the taxa at different times resulting in varying degrees of genetic differentiation across barriers with most divergences dating to the Upper Pleistocene, even when accounting for divergence with gene flow. Interestingly, when this temporal dissonance is viewed through the lens of the species‐specific ecologies, it suggests that an ecological sieve influenced whether species dispersed readily, with an ecological generalist showing the highest propensity for historical dispersal among the isolated rivers of the Brazilian coast (i.e., the most recent divergence times and frequent gene flow estimated for barriers). We discuss how our findings, and in particular what the temporal dissonance, despite common geographic passages, suggest about past dispersal structuring coastal communities as a function of ecological and paleo‐landscape sieves.